THE EFFECT OF MEDITATION SUPPORT ON STRESS LEVELS AMONG PATIENTS WITH CHRONIC KIDNEY DISEASE UNDERGOING HEMODIALYSIS - Nando Danung Priangga; Erna Erawati; Angga Sugiarto; Suharsono Suharsono (Journal of Advanced Nursing and Health Sciences, 2026)
Background: Chronic kidney disease (CKD) is a progressive disease requiring lifelong hemodialysis. Patients undergoing hemodialysis frequently experience psychological stress due to long-term treatment, dependence on dialysis machines, lifestyle changes, and physical and emotional limitations. Unmanaged stress may reduce quality of life and treatment adherence. Meditation support has been recognized as a complementary nursing intervention to reduce stress by promoting relaxation and emotional regulation. Methods: This study employed a quantitative pre-experimental design using a one-group pretest–posttest approach. A total of 36 patients with chronic kidney disease who were undergoing routine hemodialysis were selected through purposive sampling. Results: Stress levels were assessed using the Perceived Stress Scale (PSS-10) before and after a five-session meditation support intervention. Data were analyzed using the Wilcoxon Signed Rank Test. Before the intervention, 32 participants (88.9%) experienced moderate stress, 2 (5.6%) experienced mild stress, and 2 (5.6%) experienced severe stress. After the intervention, 32 participants (88.9%) experienced mild stress, while 4 participants (11.1%) remained in the moderate stress category. The median stress score decreased from 20 to 12. The Wilcoxon Signed Rank Test showed a statistically significant reduction in stress levels (Z = -5.239; p = 0.001). Meditation support significantly reduced stress levels among patients with chronic kidney disease undergoing hemodialysis. Conclusion: Meditation support may be considered an effective complementary nursing intervention to enhance psychological support and holistic nursing care for patients undergoing hemodialysis, thereby improving their overall well-being.